Sacubitril-Valsartan in Patients with Ischemic Cardiomyopathy Undergoing Off-Pump Coronary Artery Bypass Grafting—Is It Safe? - Narayan, Pradeep; Kumar, Satish; Kapoor, Lalit (The Thoracic and Cardiovascular Surgeon, 2022)
Sacubitril-valsartan has been used selectively in patients undergoing coronary artery bypass grafting (CABG) and ischemic cardiomyopathy due to safety concerns. The aim of this prospective observational study was to assess the safety profile of sacubitril-valsartan in patients with reduced ejection fraction (EF <40%) undergoing CABG. Primary outcome was tolerability and safety profile. Thirty consecutive patients undergoing CABG with EF <40% were included. No mortality or readmissions occurred during 6 months follow-up. One (3.3%) patient experienced hypotension requiring discontinuation. Mild (8.9%) elevation in blood urea nitrogen, p = 0.35; along with a significant increase in serum creatinine (0.12mg/DL), p = 0.02; and potassium (0.23 mmol/L), p 0.003 was seen during follow-up. Sacubitril-valsartan is well tolerated in patients with reduced EF undergoing CABG.
Keywords: coronary artery bypass grafting; CABG; cardiomyopathy